Design, Analysis, and Prototyping of Induction Motor for Vegetable Cutting Machine - Yildirim, Adem; Nory, Hayatullah; Yildiz, Ahmet (Institute of Electrical and Electronics Engineers Inc., 2025)
With the development of modern industry, vegetable cutting machines have become widely used in industrial kitchens, restaurants, and homes. These machines are designed to save time, increase efficiency, and ensure uniformity in vegetable preparation across various settings. To achieve this efficiency and consistency, vegetable cutting machines rely on powerful and durable motors. These motors play a critical role in driving the cutting mechanisms, ensuring precise and reliable performance in industrial kitchens and high-demand environments. In this context, this study focuses on the design, analysis, and prototyping of a squirrel-cage induction motor for large-scale industrial vegetable cutting machines. During the design process, various parameters such as nominal power, supply voltage, number of phases, and efficiency were taken into consideration. FEA results were obtained and validated with experimental results. The experimental results show that the IM design for vegetable cutting machine has met the requirements. © 2025 IEEE.
2nd International Conference on Circuits, Power, and Intelligent Systems, CCPIS 2025 -- 5 September 2025 through 7 September 2025 -- Bhubaneswar -- 217082
Keywords: electric motor design; experimental analysis; squirrel cage induction motor; vegetable cutting machine